Risk Analysis on the Construction of the Serpong – Balaraja Toll Road Section 1A (KPBU Proyek) - Rocky (Indonesian Journal of Advanced Research, 2023)
Indonesia has carried out a lot of infrastructure development, especially toll road infrastructure. To meet the needs of the public PT. Trans Bumi Serbaraja built the Serpong - Balaraja toll road. During the implementation of the development process, several risks were found that had an impact on the implementation of toll road construction. This study has the aim of analyzing, knowing the dominant risks, and countermeasures to anticipate dominant risks in the construction of the Serpong - Balaraja toll road section 1 A (KPBU Project). The results of the study show six aspects, namely: (1) nature and environment, (2) economy and finance/finance, (3) safety, (4) technical, (5) logistics/materials, (6) politics and regulations. Correlation test results of 34 variables, 11 variables are very strong, 21 variables are strong, and 2 variables are moderate. Dominant risk in variable research related to society.